Robotic Manipulator’s Expressive Movements Control Using Kinematic Redundancy - Shohei Hagane; Gentiane Venture (Machines, 2022)
In human–robot interaction (HRI), sharing emotions between the human and robot is one of the most important elements. However, market trends suggest that being able to perform productive tasks is more important than being able to express emotions in order for robots to be more accepted by society. In this study, we introduce a method of conveying emotions through a robot arm while it simultaneously executes main tasks. This method utilizes the null space control scheme to exploit the kinematic redundancy of a robot manipulator. In addition, the concept of manipulability ellipsoid is used to maximize the motion in the kinematic redundancy. The “Nextage-Open” robot was used to implement the proposed method, and HRI was recorded on video. Using these videos, a questionnaire with Pleasure–Arousal–Dominance (PAD) scale was conducted via the internet to evaluate people’s impressions of the robot’s emotions. The results suggested that even when industrial machines perform emotional behaviors within the safety standards set by the ISO/TS 15066, it is difficult to provide enough variety for each emotion to be perceived differently. However, people’s reactions to the unclear movements yielded useful and interesting results, showing the complementary roles of motion features, interaction content, prejudice toward robots, and facial expressions in understanding emotion.